Between-subject variance in the magnitude of corticomuscular coherence during tonic isometric contraction of the tibialis anterior muscle in healthy young adults - Ushiyama, Junichi; Suzuki, Tatsuya; Masakado, Yoshihisa; Hase, Kimitaka; Kimura, Akio; Liu, Meigen; Ushiba, Junichi (Journal of neurophysiology, 2011)
Oscillatory activity of the sensorimotor cortex has been reported to show coherence with muscle activity in the 15- to 35-Hz frequency band (β-band) during weak to moderate intensity of isometric contraction. The present study examined the variance of the magnitude of the corticomuscular coherence across a large number of subjects. We quantified the coherence between EEG over the sensorimotor cortex and rectified electromyogram (EMG) from the tibialis anterior muscle during tonic isometric contraction at 30% of maximal effort in 100 healthy young individuals. We estimated the maximal peak of EEG-EMG coherence (Cohmax) and the ratio of the sum of the autopower spectral density function within the β-band to that of all frequency ranges for both EEG (EEGβ-PSD) and EMG (EMGβ-PSD) signals. The frequency histogram of Cohmax across all subjects showed a broad bell-shaped continuous distribution (range, 0.048–0.816). When the coherence was thresholded at the estimated significance level of P < 0.05 (0.114), 46 out of 100 subjects showed significant EEG-EMG coherence. Cohmax occurred within the β-band in the majority of subjects who showed significant EEG-EMG coherence ( n = 43). Furthermore, Cohmax showed significant positive correlations with both EEGβ-PSD ( r = 0.575, P < 0.001) and EMGβ-PSD ( r = 0.606, P < 0.001). These data suggest that even during simple tonic isometric contraction, the strength of oscillatory coupling between the sensorimotor cortex and spinal motoneurons varies among individuals and is a contributory factor determining muscle activation patterns such as the degree of grouped discharge in muscle activity within the β-band for each subject.